Upaya Guru Dalam Pembelajaran Menulis Berbasis Pendidikan Karakter di Kelas IV Madrasah Ibtidaiyah - Siti Rokhatun; Rosnawati; Rosnah (Tamilis Synex: Multidimensional Collaboration, 2025)
The purpose of this research is to find out how teachers make efforts to learn characterbased writing, the application of character-based writing learning both face-to-face and offline, as well as the strengths and weaknesses during implementation at Madrasah IbtidaiyahThis research is a type of qualitative research, using data collection, techniques in the form of observation, interviews and documentation. We use data analysis techniques from miles and huberman. The resultsn of this study,variations of teacher in learning make hand notes. Then use of visual media to play inspiring story videos that make interested learning better reading activities in student book only. Online learning cannot be followed by all students because there are some student guardians who don’t have smartphone. Suggestions for teacher in character-learning writing-learning that have been running well are maintained and their creations are improved. So that student remain interested in writing. For school, it becomes a material for consideration in developing better character-education writing learning for students in the future. For future researchers who carry out research with a similar theme to be able to find and develop better character-education learning to write.